\((a^2+b^2)x^2+2(ac+bd)x+(c^2+d^2)=0\) দ্বিঘাত সমীকরণের বীজদ্বয় সমান হলে, প্রমাণ করি যে, \(\cfrac{a}{b}=\cfrac{c}{d}\)
\((a^2+b^2 ) x^2+2(ac+bd)x+(c^2+d^2 )=0 \)
দ্বিঘাত সমীকরণটির বীজদ্বয় সমান,অর্থাৎ নিরূপক \(=0\)
\(∴{2(ac+bd) }^2-4(a^2+b^2 )(c^2+d^2 )=0\)
বা, \(4(a^2 c^2+2abcd+b^2 d^2 )\)\(-4(a^2 c^2+a^2 d^2+b^2 c^2+b^2 d^2 )=0 \)
বা, \(4a^2 c^2+8abcd+4b^2 d^2-4a^2 c^2-4a^2 d^2\) \(-4b^2 c^2-4b^2 d^2=0 \)
বা, \(-4a^2 d^2+8abcd-4b^2 c^2=0 \)
বা, \(a^2 d^2-2abcd+b^2 c^2=0 \)
বা, \((ad)^2-2.ad.bc+(bc)^2=0 \)
বা, \((ad-bc)^2=0 \)
বা, \(ad-bc=0 \)
বা, \(ad=bc \)
বা, \(\cfrac{a}{b}=\cfrac{c}{d} \) (প্রমানিত)